Circular polarization in n-type resonant tunneling diodes with Si delta-doping in the quantum well - Herval, L.K S.; Galeti, H.V.A.; Orsi Gordo, V.; Galvao Gobato, Y.; Brasil, M.J.S.P.; Taylor, D.; Henini, M. (2014)
In this work, we have investigated magneto-transport and polarization resolved photoluminescence of a GaAs/AlGaAs resonant tunneling diode with Si delta-doping at the center of the quantum well under a magnetic field parallel to the tunnel current. Three resonant peaks were observed in the current-voltage characteristics curve (J(V)) which were associated to donor-assisted resonant tunneling, electron resonant tunneling and to phonon-assisted resonant tunneling. The optical emission from GaAs contact layers shows evidence of highly spin-polarized two-dimensional electron and hole gases which affect the spin-polarization of carriers in the well. The quantum well photoluminescence shows strong circular polarization degrees with values up to 85% under 15T at the donor assisted resonant tunneling peak voltage. Our results can be exploited for future development of voltage-controlled spintronics devices.